Penerapan Prinsip-Prinsip Manajemen Pendidikan Berbasis Al-Qur’an Dalam Meningkatkan Kedisiplinan Guru - Syahidul Ihya; Anis Fauzi (STAI Terpadu Yogyakarta, 2024)
Islamic Education Management is an effort to achieve a disciplined and directed education that is based on Islamic values and principles. However, not all Islamic educational institutions understand the management of Islamic education that is based on Islamic principles. Therefore, the purpose of this study is to analyze the form of actualization of the principles of Islamic education management in Daarul Hikmah Islamic boarding school in Bogor Regency. The method used in this research uses qualitative case studies (Field Research). The technique of collecting data sources obtained through observation and interviews to obtain relevant data about the actualization of the principles of Islamic education management. The data analysis technique process uses a data reduction process. The results of this study indicate that the form of actualization of the principles of Islamic education management is fair and efficient in planning management, responsible and dynamic in organizing management, sincere, trustworthy and responsible in implementation management, honest and fair in supervision and evaluation. This research seeks to contribute a strong theoretical basis in improving the quality of Islamic education management.